Outcomes in Brugada Syndrome Patients With Implantable Cardioverter-Defibrillators: Insights From the SGLT2 Registry - Lee, Sharen; Li, Ka Hou Christien; Zhou, Jiandong; Leung, Keith Sai Kit; Lai, Rachel Wing Chuen; Li, Guoliang; Liu, Tong; Letsas, Konstantinos P.; Mok, Ngai Shing; Zhang, Qingpeng; Tse, Gary (Frontiers in Physiology, 2020)
Background and Objectives: Brugada syndrome (BrS) is a cardiac ion channelopathy with characteristic electrocardiographic patterns, predisposing affected individuals to sudden cardiac death (SCD). Implantable cardioverter-defibrillator (ICD) is used for primary or secondary prevention in BrS, but its use remains controversial amongst low-risk asymptomatic patients. The present study aims to examine indicators for ICD implantation amongst BrS patients with different disease manifestations. Methods: This study included BrS patients who received ICDs between 1997 to 2018. The cohort was divided into three categories based on presentations before ICD implantation: asymptomatic, syncope, ventricular tachycardia/ventricular fibrillation (VT/VF). Univariate and multivariate Cox-regression analysis were performed to identify independent predictors of appropriate and inappropriate shock delivery. Results: A total of 136 consecutive patients were included with a median follow-up of 95 (IQR: 80) months. Appropriate shocks were delivered in 34 patients (25.0%) whereas inappropriate shocks were delivered in 24 patients (17.6%). Complications occurred in 30 patients (22.1%). Type 1 Brugada pattern were found to be an independent predictor of appropriate shock delivery, whilst the presence of other arrhythmia was predictive for both appropriate and inappropriate ICD shock delivery under multivariate Cox regression analysis. Conclusions: ICD therapy is effective for primary and secondary prevention of SCD in BrS. Whilst appropriate shocks occur more frequently in BrS patients presenting with VT/VF, they also occur in asymptomatic patients. Further research in risk stratification can improve patient prognosis while avoid unnecessary ICD implantation.